Topology optimization design of cast parts based on virtual temperature method. (January 2018) - Li, Quhao; Chen, Wenjiong; Liu, Shutian; Fan, Huiru
Abstract: Topology optimization has been widely used in industry for its powerful innovation ability to obtain the concept designs, which are generally unintuitive. But due to the limitation of the manufacturing processes or costs, some of these designs cannot be manufactured directly, so considering manufacturing process constraints in topology optimization becomes increasingly important. This paper presents a new method for structural topology optimization design considering the molding constraint which requires the absence of interior voids and undercuts in the cast parts. A virtual thermal diffusion problem is appropriately defined and a global thermal constraint is added into the optimization model to guarantee the cast-ability of the structural shape. The parting directions, unidirectional or multi-directional, are modeled by modifying heat dissipation boundaries and material properties. This method does not require an optimization process to start from a feasible initialization and can be applied to almost any topology optimization problems. Finite volume method is used to solve a steady-state heat equation and a parametric formulation of the conductive coefficient is given. Several examples of topology optimization of cast parts are provided to illustrate the validity and the effectiveness of the proposed method. Highlights: A new formulation of molding constraint for topology optimization is proposed. The requirement of molding constraint is realized by limiting the maximum virtual temperature. The formulation is extended to describe the multi-directional molding constraint. Examples illustrate the effectiveness of the proposed method.